Air fryer perfection : from crispy fries and juicy steaks to perfect vegetables : what to cook and how to get the best results (America's Test Kitchen, 2019)
Introduces air fryer cooking, provides ratings for different models, and presents recipes for preparing meat, seafood, and vegetables in an air fryer.